Performance of Fly Ash Concrete with Nickel Slag Fine Aggregate in the Marine Environment - Syamsul Bahri Ahmad; Rita Irmawaty; Sumarni Hamid Aly; A. Amiruddin (Civil Engineering Journal, 2022)
This research aims to assess the feasibility of the mechanical strength and the durability of the concrete containing 50% nickel slag and a combination of 15% and 30% fly ash with a water-cement ratio of 0.25 and 0.45 in a marine environment. Four types of concrete, namely OPC-sand (C) as control concrete, OPC-50GNS (S), 15FA-50GNS (F1), and 30FA-50GNS (F2) as comparison concrete, were tested with a 100×200 mm cylindrical specimen. The results showed an increase in the mechanical strength and potential resistance of the comparison concrete at the age of 28 days. While at the age of 180 days, fluctuating changes were found. The compressive strength of S concrete increased by 36.9 and 9.3% respectively, F1 concrete by 37.7% and 1.7%, F2 by 33.7% and 5.9% at ratio 0.45 and 0.25. Likewise, the value of the split tensile strength and modulus of elasticity of concrete. This result was followed by reduced porosity, sorptivity, and chloride penetration resistance as an indication of better concrete durability. Fly ash appears to have a greater positive impact on potential durability than mechanical strength at a water cement ratio of 0.25 versus 0.45. Although the chloride penetration resistance is decent, the compressive strength of concrete with a water-cement ratio of 0.45 does not qualify for application in the marine environment. In contrast, concrete with a water-cement ratio of 0.25 containing 50% nickel slag and the addition of class C fly ash up to 30% was declared suitable for application to concrete in the marine environment zone C2 according to ACI 318-19. Doi: 10.28991/CEJ-2022-08-12-010 Full Text: PDF